Systematic literature review: Exploration of ethnomathematics on Malay culture in West Kalimantan - Rustanuarsi, Ressy (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
Ethnomathematics in mathematics education has the potential to foster meaningful learning experiences by integrating students’ cultural backgrounds and lived experiences as members of specific ethnic communities. This study explores the ethnomathematical elements of Malay culture in West Kalimantan using a Systematic Literature Review (SLR) approach. Data were collected via the Publish or Perish application from journal articles indexed in Google Scholar, yielding fourteen studies published between 2017 and 2025. The review shows that ethnomathematical practices are most frequently represented in weaving, cultural traditions, games, dances, and architectural heritage. These cultural elements embed diverse mathematical concepts, with geometry and measurement as the most dominant domains, followed by algebra, probability, set theory, and logic. The results imply that Malay culture in West Kalimantan offers authentic learning resources that can enhance the meaningfulness of mathematics learning.